Answer
40.9
Step-by-step explanation:
Answer:
p = ½ (x₁ + x₂)
q = a (x₁x₂ − ¼ (x₁ + x₂)²)
Step-by-step explanation:
y = a (x − x₁) (x − x₂)
Expand:
y = a (x² − x₁x − x₂x + x₁x₂)
y = a (x² − (x₁ + x₂)x + x₁x₂)
Distribute a to the first two terms:
y = a (x² − (x₁ + x₂)x) + ax₁x₂
Complete the square:
y = a (x² − (x₁ + x₂)x + ¼(x₁ + x₂)²) + ax₁x₂ − ¼ a(x₁ + x₂)²
y = a (x − ½ (x₁ + x₂))² + a (x₁x₂ − ¼ (x₁ + x₂)²)
Therefore:
p = ½ (x₁ + x₂)
q = a (x₁x₂ − ¼ (x₁ + x₂)²)
Answer:
90 or -270
Step-by-step explanation:
Answer:
m qsr = 62°
Step-by-step explanation:
From my understanding, the question states 3 angles of a triangle
All 3 angles of a triangle are equal to 180°.
<u>Step 1: Find x</u>
<em>70 + 2x + 3x - 10 = 180°</em>
<em>70 + 5x - 10 = 180</em>
<em>5x = 180 - 60</em>
<em>x = 120/5</em>
x = 24°
<u>Step 2: Find angle qsr</u>
<em>m qsr = 3x - 10</em>
<em>m qsr = 3(24) - 10</em>
m qsr = 62°
!!
Answer:
3500
Step-by-step explanation: